2018
DOI: 10.1111/anu.12820
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid salts, protease and their combination in fish meal‐free diets improved growth, nutrient retention and digestibility of tilapia ( Oreochromis niloticus × O. aureus )

Abstract: A study was conducted to evaluate the effects of organic acid salt blend (OAB), protease complex (Pr) and their combination (OAB+Pr) in fish meal‐free diets on growth, nutrient retention and digestibility of tilapia. Five diets were designed: a positive control (PC) diet containing 80 g/kg fish meal (FM), a negative control (NC) diet containing 0 g/kg FM and 104 g/kg meat and bone meal, and three other diets supplemented with OAB (922 mg/kg), Pr (175 mg/kg) and OAB+Pr (922 mg/kg + 175 mg/kg) to the NC diet. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Blends of organic acids and their salts in free or microencapsulated forms have shown to improve growth performance of fish (40,57,58) In an in-vitro study, Mine and Boopathy [12] demonstrated EC50 values of 0.023%, 0.041%, 0.03%, and 0.066% for formic, acetic, propionic, and butyric acid, respectively against Vibrio harveyi. Romano et al [33] reported similar efficacy in V. harveyi resistance when fed OA supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blends of organic acids and their salts in free or microencapsulated forms have shown to improve growth performance of fish (40,57,58) In an in-vitro study, Mine and Boopathy [12] demonstrated EC50 values of 0.023%, 0.041%, 0.03%, and 0.066% for formic, acetic, propionic, and butyric acid, respectively against Vibrio harveyi. Romano et al [33] reported similar efficacy in V. harveyi resistance when fed OA supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…Both organic acids and their salts have been used in aquafeed for better performance and disease resistance of aquatic animals [40]. The blends of organic acids used in this study are fumaric acid, sorbic acid and citric acid.…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of 1 g/kg metalloprotease in tilapia diet (Wu, ) and 0.175 g/kg protease (AG 175 ) in rainbow trout diet (Zhang et al, ) was reported to increase intestinal villus height, protease activity and nutrient digestibility. Also in tilapia, the fish fed a fish meal‐free diet showed a decreased villus height, which could be recovered to the normal level (80 g/kg fish meal‐containing diet) by the supplementation of protease (AG 175 ) (Huan et al, ). In another study on tilapia, the supplementation of protease (AG 175 ) in low fish meal‐pelleted diet, but not in extruded diet, significantly improved the weight gain and nutrient digestibility (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The zootechnical performance parameters were assayed as described by Cho (1992), Kaushik (1998), Hisano et al (2017), and Huan et al (2018): Weight Gain, WG (g) = final body weight (g) − initial body weight (g) Thermal Growth Coefficient, TGC (g 1/3 /°C) = 1,000 × (Wfi 1/3 − Wi 1/3 )/sum degree days Feed Conversion Ratio, FCR = feed provided (g)/weight gain (g) Protein Productive Value, PPV (%) = 100 × [(final body protein x final weight) − (initial corporal protein x initial weight)]/ total protein intake Condition Factor, CF = 100 × final weight (g)/standard length (cm) 3 …”
Section: Methodsmentioning
confidence: 99%
“…This also improves nutrient availability and, consequently, diminishes nitrogen and phosphorus being excreted into the environment because of increased nutrient digestibility (Baruah et al, 2005, 2007). However, effects of organic acids on fish are variable and dependent on factors like feeding habits, age, diet composition, management, water quality, and levels of the employed acids (Castillo, Rosales, Pohlenz, & Gatlin, 2014; Huan et al, 2018; Ng & Koh, 2016).…”
Section: Introductionmentioning
confidence: 99%